2009
DOI: 10.1007/s11033-009-9470-1
|View full text |Cite
|
Sign up to set email alerts
|

DAZL binds to 3′UTR of Tex19.1 mRNAs and regulates Tex19.1 expression

Abstract: Spermatogenesis is a complex process subject to strict controls at both levels of transcription and translation. It has been proposed that DAZL protein binds to RNA in the cytoplasm of germ cells and controls spermatogenesis. In male mice, loss of Dazl results in numerous defects throughout the mitotic and meiotic process of germ cell development. Tex19.1 also plays an important role during spermatogenesis and Tex19.1(-/-) knockout males exhibit impaired spermatogenesis. Mouse DAZL protein can bind to 3'UTR of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
1
13
1
Order By: Relevance
“…It is unlikely that this regulatory mechanism functions in mature mouse oocytes in view of the recent reports that miRNA function is inactivated at this stage of oocyte development (Ma et al 2010;Suh et al 2010). At variance with our finding that both 39UTR mutagenesis and MO downregulation of DAZL decrease Tex19.1 translation, a study suggested that Dazl represses Tex19.1 translation when introduced in zebrafish oocytes (Zeng et al 2009). Although removal of DAZL elements from the 39UTR of Tex19.1 impairs accumulation of the reporter in MII oocytes, it also causes a small increase in reporter translation in GV, suggesting that this element may mediate translational repression at this stage.…”
Section: Discussioncontrasting
confidence: 94%
“…It is unlikely that this regulatory mechanism functions in mature mouse oocytes in view of the recent reports that miRNA function is inactivated at this stage of oocyte development (Ma et al 2010;Suh et al 2010). At variance with our finding that both 39UTR mutagenesis and MO downregulation of DAZL decrease Tex19.1 translation, a study suggested that Dazl represses Tex19.1 translation when introduced in zebrafish oocytes (Zeng et al 2009). Although removal of DAZL elements from the 39UTR of Tex19.1 impairs accumulation of the reporter in MII oocytes, it also causes a small increase in reporter translation in GV, suggesting that this element may mediate translational repression at this stage.…”
Section: Discussioncontrasting
confidence: 94%
“…Numerous studies have identified putative mRNA targets of DAZL [10,11,42-46], however only a limited number of these have been validated in vivo [9,10]. In contrast, little is known about the identity of the mRNA targets of BOLL [47], and whether the motif to which it binds is similar to the GU-rich sequences bound by DAZL remains unclear [48].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, DAZL acts by inducing translational activation of its target mRNAs, but its binding site, a GUU triplet, has not been reported to convey cytoplasmic polyadenylation in Xenopus oocytes . In zebrafish embryos, DAZL binding regulates the stability of its target mRNAs, presumably to restrict their expression to the future germ cells, as this protein is normally germ cell specific . In one such study, DAZL was reported to overcome miR‐430 mediated destabilization by the 3′ UTR of its own mRNA.…”
Section: Cytoplasmic Polyadenylation Of Mrnas In Germ Cells and Embryosmentioning
confidence: 80%